PENGALAMAN BERDUKA PASCA PERISTIWA BUNUH DIRI IBU - Nabila Ratu; Yohanis Franz La Kahija (Faculty of Psychology, Diponegoro University, 2017)
In this modern era, suicide holds status as one of the biggest public health problems in the world. According to data compiled by the World Health Organization (WHO), in 2015 there were 788,000 deaths from suicide worldwide. A phrase